2007
DOI: 10.1007/s10705-007-9146-y
|View full text |Cite
|
Sign up to set email alerts
|

Millet nutrient use efficiency as affected by natural soil fertility, mineral fertilizer use and rainfall in the West African Sahel

Abstract: Field experiments were designed to investigate the effectiveness of integrated soil fertility management (ISFM), comparing fertilizer use efficiency and its impact on millet, cultivated close to the homestead (''infields'') and away from the homestead (''outfields''). Millet yields and response to N (0, 30, and 60 kg ha -1 ) and P (0, 15, and 30 kg ha -1 ) were determined on nine infields and nine outfields over a period of 3 years (from 1999 to 2001) in the southern Sahel of Niger. Rainfall was 650, 470, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 16 publications
(16 reference statements)
3
22
0
Order By: Relevance
“…However, all treatments also supplied small quantities of N, and in the case of NPK, potassium. Regarding the latter, potassium is generally not considered a limiting nutrient for commonly encountered millet productivity levels in the Sahelian zone of Niger, in part because of substantial K inputs from Harmattan dust (Fofana et al, 2007;Herrmann et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, all treatments also supplied small quantities of N, and in the case of NPK, potassium. Regarding the latter, potassium is generally not considered a limiting nutrient for commonly encountered millet productivity levels in the Sahelian zone of Niger, in part because of substantial K inputs from Harmattan dust (Fofana et al, 2007;Herrmann et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Liu et al (2008) found that, under a relatively high background soil K fertility circumstance, applying fertilizer K significantly increased yield of tomato supplied with high N. Without fertilizer K input, high yield potential driven by high N input might deplete soil K supply. The deficient K in the control treatment substantially decreased photosynthesis (Kanai et al 2011), and limited growth of crops even supplied with adequate N (Fofana et al 2008), resulting in significantly lower N uptake in the K control treatment. The K deficiency was also reported to depress stem diameter expansion and then limited the translocation of assimilates to fruits (Kanai et al 2011), lowering NHI in the K control treatment.…”
Section: Fertilizer K Effectsmentioning
confidence: 99%
“…Soil organic carbon contents of between 11 and 22 g/kg have been observed in home gardens compared with 2-5 g/kg soil in bush fields. Fofana et al (2006) in a comparative study at Karabédji-Niger on degraded lands (bush fields) and non degraded (infields) have observed that millet grain yield across years and fertilizer averaged only 800 kg/ha in bush fields and 1,360 kg/ha on infields. Recovery of fertilizer N (RFN) applied varied considerably and ranged from 17% to 23% on bush fields and from 34% to 37% on infields.…”
Section: Long-term Millet Trials Phosphorus Nitrogen Crop Residue (mentioning
confidence: 99%